Maternal genital chlamydial infection as a cause of neonatal conjunctivitis. Issue 624 (October 1977) - Hobson, D.; Rees, E.
Abstract : Infections of the cervix with Chlamydia trachomatis are common, at least in those groups of sexually active women of child-bearing age who are seen in STD (sexually-transmitted diseases) clinics. Persistent untreated infection presents a hazard to the women themselves during pregnancy and to their infants who may develop chlamydial conjunctivitis. The clinical and laboratory findings in 1009 women and in 103 infants with conjunctivitis are presented. Practical problems of diagnosis and control of neonatal chlaymdial conjunctivitis are described. A possible association between prematurity and chlamydial infection is discussed.